Assassination Classroom: Time for an Opportunity - Vol 8 08, Time for an opportunity - Matsui, Yusei, 1981-; Miyaki, Tetsuichiro; Turnage, Bryant (San Francisco, CA : VIZ Media, LLC, 2016)
The 3-E students storm the enemy, who has launched a deadly biological attack. Their path is blocked by three master assassins.
Rated T+ for older teen; parental advisory.
Translated from Japanese.
Keywords: Students -- Comic books, strips, etc; Young adult fiction; Assassins -- Comic books, strips, etc; Young adult fiction; Schools -- Comic books, strips, etc; Young adult fiction; Assassination -- Comic books, strips, etc; Young adult fiction; Attempted assassination -- Comic books, strips, etc; Young adult fiction; Teachers -- Comic books, strips, etc; Young adult fiction; Extraterrestrial beings -- Comic books, strips, etc; Young adult fiction; Graphic novels; Manga; Science fiction comics